2007
DOI: 10.1007/s10517-007-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hemostatic parameters after intranasal administration of peptide Pro-Gly-Pro

Abstract: Anticoagulant activity, total and nonenzymatic fibrinolytic activity, and tissue plasminogen activator activity increased, while platelet aggregation and activity of factor XIIIa in rat blood plasma decreased over 3 h after single intranasal administration of proline-containing peptide Pro-Gly-Pro. Hemostatic parameters in rats 24 h after single administration of this peptide did not differ from the control level observed in animals receiving 0.85% NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Moreover, PGP also has the ability to block the angiotensin-converting enzyme (Wang et al 2011), one of the most important proatherogenic factors that catalyzes the reaction of angiotensin II formation and promotes vascular wall remodeling (Montezano et al 2014). A number of Russian studies have also identified the antithrombotic and antiaggregant properties of PGP (Pastorova et al 2001;Lyapina et al 2007;Liapina et al 2010), making its adherence to PHBSP even more promising. The key question remains the nature of embedding RGD and PGP motifs in the base molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PGP also has the ability to block the angiotensin-converting enzyme (Wang et al 2011), one of the most important proatherogenic factors that catalyzes the reaction of angiotensin II formation and promotes vascular wall remodeling (Montezano et al 2014). A number of Russian studies have also identified the antithrombotic and antiaggregant properties of PGP (Pastorova et al 2001;Lyapina et al 2007;Liapina et al 2010), making its adherence to PHBSP even more promising. The key question remains the nature of embedding RGD and PGP motifs in the base molecule.…”
Section: Resultsmentioning
confidence: 99%
“…В ряде отечественных работ также были выявлены антитромботические и антиагрегантные свойства другого вспомогательного аминокислотного трипептида Pro-Gly-Pro. [23][24][25]. Кроме того, Pro-Gly-Pro стабилизирует молекулу в биологических средах за счет ингибирования активности протеолитических ферментов [26] и обладает способностью блокировать ангиотензин-превращающий фермент [27], один из важнейших проатерогенных факторов, который катализирует реакцию образования ангиотензина II и способствует ремоделированию сосудистой стенки [28].…”
Section: Discussionunclassified
“…Moreover, PGP can also block the angiotensin-converting enzyme [ 50 ], one of the most important pro-atherogenic factors that catalyze the formation of angiotensin II, increasing the risk of brain stroke [ 51 ]. Several studies have also identified antithrombotic and antiplatelet properties of PGP [ 52 , 53 , 54 ], which makes it even more promising to join pHBSP. The key question remains the nature of embedding RGD and PGP motifs in the base molecule.…”
Section: Discussionmentioning
confidence: 99%